2001
DOI: 10.1155/2001/640796
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Celiac Disease in Patients with Type 1 Diabetes Detected by Antibodies to Endomysium and Tissue Transglutaminase

Abstract: At least 14 new cases of CD were detected in addition to four known cases, yielding an overall biopsy-confirmed prevalence of CD of 7.7% (18 of 233). The present study confirms that CD is as prevalent in the pediatric type 1 diabetic population in British Columbia as it is in Europe. Serological screening of these children is important because many children have no symptoms or signs suggestive of CD. This study suggests that tTG serology may also be useful in monitoring response and compliance with a gluten-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 23 publications
2
67
1
Order By: Relevance
“…Despite many similarities between DM1 and CD, such as underlying genetic susceptibility associated with HLA class II and autoimmune phenomena, the prevalence rate of CD in DM1 appears to differ greatly in different geographical areas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Both diseases were associated with a high frequency of HLA DQA1* 0501 and DQB1*0201 (DQ2) molecules worldwide (5).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many similarities between DM1 and CD, such as underlying genetic susceptibility associated with HLA class II and autoimmune phenomena, the prevalence rate of CD in DM1 appears to differ greatly in different geographical areas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Both diseases were associated with a high frequency of HLA DQA1* 0501 and DQB1*0201 (DQ2) molecules worldwide (5).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine receptor antibodies were measured using a modified radioimmunoprecipitation assay [6] . Approval to test samples for endomysial antibodies and IgA tissue transglutaminase antibody concentrations was obtained through the Clinical Research Ethics Board at UBC as previously noted [7,8] .…”
Section: Special Serological Studiesmentioning
confidence: 99%
“…A recent TTG prospective study [7] in children and adolescents with type 1 diabetes evaluated TTG antibody titres in 125 males and 108 females followed in a pediatric diabetes center. Altogether, 26 patients, including 15 males and 11 females, had positive TTG titres and, of these, 19 were also positive for EMA.…”
Section: Pancreatic Endocrine Changesmentioning
confidence: 99%
“…In those positive for both TTG and EMA, small intestinal biopsies were done. Histopathological abnormalities described in celiac disease were detected ranging from increased numbers of intraepithelial lymphocytes to severe crypt hyperplastic villous atrophy (Marsh 3 lesion) [7] . These studies also suggested that serial TTG serological measurements in insulin-dependent diabetics might play a role in monitoring their serological responses as well as the compliance to the gluten-free diet.…”
Section: Pancreatic Endocrine Changesmentioning
confidence: 99%